Non-formal financing for the entrepreneurship of a sme (small and medium-sized enterprise) - Cabanillas Beltrán, Mayra Alejandra (2018)
The aim of the research work is to identify the types of financing different from banking and suitable for a SME. When undertaking a business, it is necessary to collect as much information as possible about the adequate financing, based on the needs and payment capacity of each entrepreneur; he should know that there's not only exist financial support opportunities from bank entities, he can look for other alternatives. It was identified that the most used and reliable type of non-formal financing are the “Juntas” or “Panderos” that allows the entrepreneur to don't depend on banking entities.